The Influence of Green Performance and Intellectual Capital on Tax Avoidance - Sailendra, Sailendra (Journal of Business Management and Economic Development, 2023)
The purpose of this study is to examine the influence of green performance and intellectual capital on tax avoidance, focusing on intellectual capital as a moderating variable. The research sample consists of 264 observations from 45 publicly listed groups of green companies (proper) on the Indonesia Stock Exchange from 2017 to 2022. The data were collected from the website of the Indonesian Stock Exchange (IDX), the Ministry of Environment and Forestry of the Republic of Indonesia, and the websites of the companies. The data were analyzed using structural equation modeling (SEM) to test the research hypotheses. The results of the hypothesis test indicate that environmental performance does not affect tax avoidance, but shows a negative relationship. Similarly, intellectual capital does not affect tax avoidance but also has a negative relationship. In addition, intellectual capital shows no moderating but negative directional sign between green performance and tax avoidance. The moderating function of intellectual capital reduces the tendency of tax avoidance in firms with high green performance. The results of this study suggest that intellectual capital strengthens environmentally and socially responsible behavior. Firms with lower intellectual capabilities tend to engage in tax avoidance practices. This research contributes to the literature on the drivers of corporate tax avoidance and sustainable practices, which can provide insights into how intellectual capital drives responsible tax compliance behavior in green companies. The results of this study have implications for corporate tax policy and motivate ethical behavior within the firm.